The urgence of Indonesian Penal Code (KUHP) reform to realize humanistic-based imprisonment - Isnawati, Muridah (Borobudur Law Review, 2021)
The development of law shall proportionally handled in all aspects of life and relevant to the interests of the community. Modern community is closely related to the era of information technology which is popular with the era of disruption or the industrial revolution 4.0. This study aims to analyze the concept of a humanistic-based criminal approach and imprisonment in the era of the industrial revolution 4.0. This study uses normative legal research with statute and conceptual approach. The results shows that the development of information technology has been proven to bring many changes in the current pattern of human life as well as the existence of law and criminal law. The swiftly transformation regarding Industrial Revolution 4.0 also demand legal reform as a challenge. Imprisonment as an important aspect of Criminal Law shall accordance with the existence of this 4.0 industrial revolution era. Seeing these conditions, it is necessary to harmonize the laws and regulation in the era of the industrial revolution 4.0 which is an effort to reform criminal and humanistic-based prisons in the era of the industrial revolution 4.0.